0644 An Educational and Behavioral Intervention Failed to Improve PAP Use Among Veterans With Spinal Cord Injuries and Diseases: Results of a Randomized Controlled Trial. (27th May 2020) - Martin, J L; Sankari, A; Salloum, A; Zeineddine, S; Arvai, K; Henzel, M K; Shamim-Uzzaman, Q; May, A; Fung, C H; Mitchell, M N; Strohl, K P; Badr, M S
Abstract: Introduction: Sleep disordered breathing (SDB) is common among individuals with spinal cord injuries or diseases (SCI/D), many of whom are military Veterans, and physical limitations make use of positive airway pressure (PAP) therapy challenging. This study sought to test the effects of an educational and behavioral intervention to improve PAP adherence among Veterans with SCI/D over the first 3 months of use. Methods: 63 Veterans (mean age=60.7(10.2) years; 92% male) with SCI/D (33 SCI, 30 SCD; 25 cervical involvement; 38 thoracic and below) and SDB (23 with AHI 5-15; 40 with AHI≥15) who received PAP treatment (CPAP or BPAP) were randomly assigned to receive a comprehensive 3-month intervention (INT) or an equal attention control (EAC). INT and EAC both included 1 face-to-face session (week 1) and 5 additional telephone sessions (weeks 2, 3, 4, 8 and 12). Main outcome measures were PAP use over the first 3 months: nights of use, nights of use ≥4 hours, and mean hours of use per night. Repeated measures ANCOVA models were used to test the differences between INT and EAC over the first 3 months of treatment. Results: Number of nights with ≥4 hours of use in months 1-3 was 9, 7, and 6 nights in the INT and 8, 5 and 4 nights in the EAC (p's≥.37), respectively. There were no significant differences between INT and EAC for number of nights with any use (p's≥.24), or mean hours of use per night (p's≥.30). All 3 PAP use variables declined over time in both groups. Conclusion: Sustained use of PAP therapy was difficult to achieve among those with SCI/D, and a 6-session behavioral intervention did not lead to significant improvements in use. Even when relatively high levels of initial use are achieved, this is difficult to sustain over time. Future studies should explore whether SCI/D patients experience significant symptom relief with PAP, and if so, whether home-based interventions or more intensive face-to-face PAP adherence programs will be effective. Support: VA Rehabilitation Research and Development Service, Merit Review (1RX002116; PI: Badr); NIH/NHLBI K24 HL143055 (Martin).